A coercion-resistant online voting protocol based on blind signatures and fake credentials - Silva, Vítor Rezende; Barros, Charles F. de (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg), 2023)
In this paper, we present an initial proposal for a practical implementation of an online voting system based on blind signatures, to provide both ballot secrecy and integrity, together with universal verifiability. Moreover, the proposed system offers coercion-resistance by means of a credential scheme based on fake passwords, that the voter can use when under coercion. The idea is that fake passwords seem indistinguishable from valid passwords, and by allowing the voter to use an arbitrary number of fake passwords, no adversary is capable of determining if a coerced voter is casting a valid ballot or a fake ballot.